A qualitative study of Chinese teacher’s perceptions and practices of meritocracy - Xiaoxue Sun; Lan Shi (PLoS ONE, 2025)
China has a long history of meritocracy, but as social inequality grows, people are increasingly questioning whether hard work promises a better life, even as national policies and mainstream media spare no effort to promote meritocratic narratives. In response, how do people interpret their lives and act within the conflict context between social realities and political forces? On the basis of semi-structured interviews with teachers in different types of schools, this paper explores how teachers interpret meritocracy and navigate it in their teaching practices. The results indicate that teachers show a dual attitude toward meritocracy. On the one hand, they believe that effort and ability are crucial to occupational and educational success, yet on the other hand, they also acknowledge the influence of guanxi on employment and the noticeable educational disparities caused by family background. Teachers have different approaches to balancing meritocratic and nonmeritocratic factors in their teaching. Teachers who limit their responsibilities regarding student growth offer verbal advice. The majority of teachers guide students to focus on working to redress the gap derived from nonmeritocratic factors while also warning students not to place too much hope on agency. Teachers’ practices inevitably contribute to social inequality. This paper underscores that in an environment lacking redistribution mechanisms, meritocracy for teachers is more of a pragmatic calculation than a belief.